Transformasi Kapasitas Kunci dan Nilai dalam Pendidikan Karakter dan Moral di Era Digital - Ririn Linawati; Fuad Abdillah; Herry Sulendro Mangiri; Nurul Burhan (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2026)
The Development Of Digital Technology Has Introduced New Ethical Risks, Such As Polarization, Misinformation, And The Misuse Of Data, That Exacerbate The Moral Vulnerability Of Learners, Primarily Due To Technological Affordances Like Algorithms And Manipulative Interface Designs. In This Context, Traditional Value-Based Character Education Faces The Challenge Of Relevance If It Is Not Recontextualized. This Study Aims To (1) Analyze Three Key Digital Capacities: Cyber-Wisdom, Technomoral Resilience, And Digital Agency In Response To Bold Ethical Risks; (2) Identify The Need For The Transformation Of Traditional Values In Character Education; And (3) Design A Theoretical-Pedagogical Framework To Integrate Such Capacities Into The Curriculum. Through A Systematic Literature Study Of The 2015–2025 Period, Encompassing Literature From Google Scholar, Scopus, And Sinta, The Findings Reveal That These Three Capacities Represent A Contemporary Evolution Of Phronesis, Moral Virtues, And Individual Character Within The Aristotelian Tradition. Character Education Needs To Shift From A Normative-Affective Approach To A Reflective-Agency Model That Emphasizes Moral Autonomy, Digital Accountability, And Moral Imagination. This Research Contributes To The Reconceptualization Of Character Education Through The Integration Of Virtue Ethics And Technological Philosophy, While Offering A Framework For Curricular Implementation That Applies To The Context Of Indonesian Education In The Digital Era.